Econometric study on the impact of EU loan guarantee financial instruments on growth and jobs of SMEs - Fabio Bertoni; Julien Brault; Massimo G. Colombo; Anita Quas; Simone Signore (European Investment Fund (EIF), 2019)
This working paper investigates the economic effects of guaranteed loans granted under the EU programmes MAP and CIP on SMEs' growth in Italy, the Benelux and the Nordic countries (Denmark, Finland, Norway and Sweden) from 2002 to 2016. In these macro-regions, the facilities supported 174,107 loans to SMEs, for a total of EUR 15.58bn. Using a sample of these loans with corresponding firm-level data, this study estimates the average treatment effect on firms' growth, profitability, assets intangibility and survival. The analysis compares beneficiary SMEs to similar firms that were not supported by the programmes, identified through coarsened exact matching (CEM) and propensity score matching (PSM). Overall, guaranteed loans are found to positively affect the growth in assets (+19.6 percentage points over the two years after the end of the signature year), sales (+14.8 percentage points), employment (+16.9 percentage points) and the share of intangible assets (+1 percentage point). No significant effect on profits is observed. Beneficiary SMEs also have lower bankruptcy rates compared to control firms. Consistent with the literature on financing constraints, positive effects are stronger for smaller, younger SMEs. Treatment effects are more pronounced in the Benelux and Nordic countries, mostly due to the sample composition of treated firms in each macro-region.
Keywords: G2; H25; O16; 330; EIF; credit guarantees; credit constraints; real effects; small and medium-sized enterprises